Ardi, Budhi Pembuatan Produk Bioplastik sebagai Proyek dalam Pembelajaran STEM-PjBL untuk Meningkatkan Kemampuan Berpikir Kritis Siswa : pembelajaran proyek bioplastik - Ardi, Diana Melidyah; Budhi, Henry Setya (PendIPA Journal of Science Education, 2025)
This research project aimed to obtain data on learning outcomes using the Project-Based Learning (PjBL) method related to STEM activities in honing students' critical thinking skills in bioplastic manufacturing projects. This research used quantitative method with one group pretest-posttest design. The research targets were VII A students of SMP Negeri 1 Nalumsari as many as 22 students. The research instruments were pretest and posttest tests with analysis of homogeneity test, normality test, and N-Gain test. The test results showed that all data were normally distributed and homogeneous, so it was feasible to analyze further. The overall N-Gain average was 0.6029 (medium category), indicating an increase in critical thinking by 60.29% after learning. The indicators with the highest improvement were problem identification and analysis, while problem solving and drawing conclusions experienced low improvement. Although there are differences in each indicator, all stages of PjBL from problem determination to experience evaluation are proven to contribute to the development of students' critical thinking. This research shows that STEM-PjBL through bioplastic projects can be an alternative to contextualized science learning and 21st century skill oriented.